Research on Over-Strength of RC Shear Wall Structure - Song-Hun Hong; Kwang-Chol Ri (Talenta Publisher, 2023)
Building is of a high degree of statically indeterminacy and should be designed with strict requirement on stability, load combinations, aseismic measures and so on. And in some cases, designers tend to decide dimensions and reinforcement over standards intentionally. Thus, seismic capacity exceeds standard required to design Stage in the well-operated structure abided by design code. This results in considering the problem of over-strength of buildings with high requirement of seismic demand and economic efficiency. In this paper, we decided the minimum value of over-strength factor of RC shear wall structure with evaluating the over-strength designed strictly according to Design Code of DPRK.